Effects of Huazhuo Jiedu Shugan Decoction on Cognitive and Emotional Disorders in a Rat Model of Epilepsy: Possible Involvement of AC-cAMP-CREB Signaling and NPY Expression. (13th December 2019) - Ping, Xin; Qin, Shao-Kun; Liu, Shu-Ning; Lu, Ye; Zhao, Ya-Nan; Cao, Ya-Fei; Zhang, Yan-Hong; Zhang, Shao-Dan; Chu, Li; Pei, Lin
Abstract : Background . Huazhuo Jiedu Shugan decoction (HJSD), a traditional Chinese medicine (TCM), has been used to treat epileptic seizures for many years. Some ingredients in these herbs have been demonstrated to be effective for the treatment of brain damage caused by epilepsy. Aim of the Study . The object of the study is to determine the effects of HJSD on cognitive and emotional disorders in a rat model of epilepsy. Materials and Methods . After a predetermined time period, rats were intraperitoneally injected with pentylenetetrazol and observed in different phases of convulsions. The cognitive and emotional changes in the epileptic rats were assessed using behavioral and immunohistochemical tests. Results . Compared with the epilepsy group, the seizure grade was reduced and seizure latency was prolonged following HJSD-H treatment (P < 0.01 ). Compared with the control group, the epilepsy group displayed marked worse performance on the animal behavior tests (P < 0.05 ) and the HJSD-H group displayed improved behavioral performance (P < 0.05 ). After HJSD-H treatment, the expression of adenylate cyclase (AC), cyclic adenosine monophosphate (cAMP), cAMP-response element binding protein (CREB), and neuropeptide Y (NPY) immunoreactive cells markedly increased in the hippocampus, compared with that of the epilepsy group (P < 0.05 ). Conclusions . The current results demonstrate that HJSD treatment in epileptic rats markedly inhibits epileptic seizures and improves cognitive and emotional disorders, which may be related to the regulation of AC-cAMP-CREB signaling and NPY expression in the hippocampus. The effects of the HJSD treatment may provide a foundation for the use of HJSD as a prescription medicinal herb in the TCM for the treatment of epilepsy.